Optimizing Evacuation Routes During Volcanic Eruptions: A Comparative Analysis of Pathfinding Algorithms around Mount Sinabung - Erikson Sinukaban; Franky Sotar Sitohang (Vertex, 2024)
This research explores the optimization of evacuation routes amid volcanic eruptions around Mount Sinabung, employing sophisticated pathfinding algorithms the Bellman Ford and Floyd Warshall algorithms. Leveraging diverse datasets encompassing geographical, demographic, and historical information, the study aims to identify optimal evacuation paths considering factors such as terrain conditions, population distribution, and real-time adaptability. The study's methodology involves the integration of geospatial data, historical eruption records, and infrastructure details into structured graph representations, enabling algorithmic computations to determine efficient evacuation routes. Comparative analyses of the Bellman Ford and Floyd Warshall algorithms highlight their strengths, limitations, and applicability in dynamic volcanic scenarios, offering nuanced insights into their performance. The findings reveal optimized evacuation routes that prioritize safety, efficiency, and inclusivity, catering to diverse demographic needs. Additionally, future research directions outlined for refining pathfinding algorithms stress the importance of interdisciplinary collaboration, technological advancements, and community-centric approaches in enhancing disaster preparedness and response strategies. This research contributes to the evolving landscape of disaster management by offering evidence-based insights, actionable recommendations, and a roadmap for policymakers, emergency responders, and local authorities.